ORGANIZATIONAL COMMITMENT, SATISFACTION AND PERFORMANCE OF LECTURER (MODEL REGRESSION BY GENDER OF MAN) - Hazriyanto, Badaruddin Ibrahim, Frangky Silitonga (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The lecturers are tobe the most important thing in the Universities as an educational problem here. So many improvement that university did to improve the quality of the university. There are included by increasing job satisfaction, building commitment and improving performance where they are conserned by universities. The variables in this research are commitment, satisfaction and performance so they are based on the man gender. The type of methodology is qualitative research where data analysis tool is analysed by SPSS statistical which uses some questioners. The Questiones is divided become 3 parts, they are 18 items for commitment, satisfaction is 12 items, and performance is 16 items. The result of sampling method is 53 lecturers at Putera Batam University in Riau Islands province of Indonesia. All of the sample is man that is a gender analysis.The results of the research is addressed that organizational commitment to a positive performance is not singnificant, job satisfaction to positive performance is significant, commitment and job satisfaction to the positive performance is significant. If the organizational commitment and job satisfaction are high so perfomance will be high, that is what to improve lecturers’ perfomance correlates with their commitments and satisfaction. For further reseach is need to be developed with a view of the woman.